A pH-responsive polyelectrolyte multilayer film with tunable interfacial properties. (1st February 2021) - Jiang, Tao; Moghaddam, Saeed Zajforoushan; Thormann, Esben
Abstract: We report a facile and versatile approach to fabricate polyelectrolyte multilayer (PEM) films with a chemically modifiable outer surface. A PEM film was prepared by layer-by-layer assembly of poly (2-aminoethyl methacrylate) (PAMA) and polymethacrylic acid (PMAA), terminated with a partially tert-butyloxycarbonyl (Boc)-protected random copolymer (PAMA-co-PBocAMA) as the final layer. The obtained PEM film was then cross-linked and the free amino groups in the PEM film were quenched using EDC/NHS chemistry. The outer layer of the film was then treated via a deprotection reaction, affording free amino groups selectively located at the film surface. As a proof of concept study, these functional groups were used to modify the film surface with two model hydrophilic and hydrophobic compounds, which tuned the wettability of the PEM. Graphical abstract: Image 1 Highlights: Polyelectrolyte multilayer films with a chemically modifiable outer surface. Single component polyelectrolyte layer films obtained by a layer-by-layer approach. Hydrophobic and hydrophilic polyelectrolyte multilayer films. Surface functionalization of polyelectrolyte multilayer films.